2021
DOI: 10.3390/medicina57101035
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Newborn Screening on Clinical Presentation of Congenital Adrenal Hyperplasia

Abstract: Background and Objectives: The main reason for Newborn screening (NBS) for congenital adrenal hyperplasia (CAH) is to prevent adrenal insufficiency that can lead to life-threatening conditions. On the other hand, screening programs are not always sensitive and effective enough to detect the disease. We aimed to evaluate impact of the national NBS on the clinical presentation of patients with CAH in Lithuania. Materials and Methods: A retrospective study was performed on data of 88 patients with CAH from 1989 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…A project to compare TSH levels in newborns to evaluate iodine status showed mild iodine deficiency in some areas and a need to reevaluate the proposed satisfactory level of TSH vs. iodine level [ 891 ]. A 2021 review of CAH case detection showed 100% sensitivity and specificity of NBS in detecting classical SW CAH, but a poor (4%) positive predictive value [ 892 ].…”
Section: Resultsmentioning
confidence: 99%
“…A project to compare TSH levels in newborns to evaluate iodine status showed mild iodine deficiency in some areas and a need to reevaluate the proposed satisfactory level of TSH vs. iodine level [ 891 ]. A 2021 review of CAH case detection showed 100% sensitivity and specificity of NBS in detecting classical SW CAH, but a poor (4%) positive predictive value [ 892 ].…”
Section: Resultsmentioning
confidence: 99%
“…Newborn screening (NBS) dried blood spot (DBS) steroid analysis for congenital adrenal hyperplasia (CAH) due to classical 21-hydroxylase deficiency is performed by several countries globally [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. 17-Hydroxyprogesterone (17OHP) has been the principal steroid measured in blood for screening and diagnosis of CAH because in 21-hydroxylase deficiency, it is the immediate precursor (i.e., 17OHP).…”
Section: Introductionmentioning
confidence: 99%